Estimation Model Peak Ground Acceleration at Bedrock and Surface of The Pasaman Barat Earthquake on February 25, 2022 M_w 6.1 - Furqon Dawam Raharjo; Syafriani Syafriani; Suaidi Ahadi (Department of Physics, Sebelas Maret University, 2024)
The earthquake occured on february 25, 2022 in West Pasaman, Province West Sumatera with momen magnitude Mw6.1, produced strong ground motion so that many several buildings were damaged. The peak ground acceleration (PGA) represents its level ground acceleration in bedrock and peak surface acceleration (PGAm) describes the acceleration value on the surface which depends on the amplification factor and the type of soil classification. Information peak ground acceleration (PGA) and peak surface acceleration (PGAm) values plays an important role in describing the level of damage due to earthquake events. The purpose this study for determine the peak ground acceleration (PGA) and peak surface acceleration (PGAm) for West Pasaman earthquake Mw6.1 using boore (1997) attenuation model. In this study using parameter data main earthquake and then peak ground acceleration (PGA) value calculated each grid points and then analysis peak surface acceleration (PGAm) value is based on the effect of site class from information Vs30 USGS model on peak ground acceleration (PGA) at bedrock from SNI 1726 : 2012. The result in this study showed peak ground acceleration and peak surface acceleration value in due West Pasaman earthquake ranged between 0.066 - 0.345 g and 0.223 - 0.627 g. The areas affected by heavy damage occured in Kajai, Rimbo Panti, Malampah and Tigo Nagari Subdistrict with peak ground acceleration and peak surface acceleration value around 0.115 - 0,345 g and 0.423 - 0.627 g respectively and was dominated with type site class moderate soil (SD) based on Vs30 data form USGS model.